EPAC1 activation by cAMP stabilizes CFTR at the membrane by promoting its interaction with NHERF1 - Lobo, MJ; Amaral, MD; Zaccolo, M; Farinha, CM (Company of Biologists, 2016)
Cyclic AMP (cAMP) activates protein kinase A (PKA) but also the guanine nucleotide exchange factor 'exchange protein directly activated by cAMP' (EPAC1; also known as RAPGEF3). Although phosphorylation by PKA is known to regulate CFTR channel gating - the protein defective in cystic fibrosis - the contribution of EPAC1 to CFTR regulation remains largely undefined. Here, we demonstrate that in human airway epithelial cells, cAMP signaling through EPAC1 promotes CFTR stabilization at the plasma membrane by attenuating its endocytosis, independently of PKA activation. EPAC1 and CFTR colocalize and interact through protein adaptor NHERF1 (also known as SLC9A3R1). This interaction is promoted by EPAC1 activation, triggering its translocation to the plasma membrane and binding to NHERF1. Our findings identify a new CFTR-interacting protein and demonstrate that cAMP activates CFTR through two different but complementary pathways - the well-known PKA-dependent channel gating pathway and a new mechanism regulating endocytosis that involves EPAC1. The latter might constitute a novel therapeutic target for treatment of cystic fibrosis.